2015
DOI: 10.1063/1.4938581
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale simulation of reactive pressed energetic materials under shock loading

Abstract: Numerical studies of PBXs are important for understanding the relationship between their mechanical properties and explosive behavior. The objective of this research is to analyze the thermomechanical response of HMX/Estane, a Polymer-Bonded Explosive (PBX), over a range of grain volume fractions at room temperature (300 K) and ε = 16,667 s-1. The analysis focuses on the correlation between grain-level failure mechanisms and the overall response using a Lagrangian cohesive finite element method (CFEM) framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 37 publications
3
52
0
Order By: Relevance
“…While the phenomenon of void collapse has been extensively studied via experiments [9][10][11] and numerical simulations [6,8,[12][13][14][15][16][17][18], the focus has primarily been on ideal-shaped voids such as cylindrical, elliptical, conical, or spherical voids. There have only been a few published papers that have studied deviations from cylindrical shape.…”
Section: Importance Of Void Shape and Void-void Interactions In Energmentioning
confidence: 99%
“…While the phenomenon of void collapse has been extensively studied via experiments [9][10][11] and numerical simulations [6,8,[12][13][14][15][16][17][18], the focus has primarily been on ideal-shaped voids such as cylindrical, elliptical, conical, or spherical voids. There have only been a few published papers that have studied deviations from cylindrical shape.…”
Section: Importance Of Void Shape and Void-void Interactions In Energmentioning
confidence: 99%
“…With advanced computing technology, to perform meso-resolved simulations of detonation phenomena in high explosives has recently become feasible. Via performing meso-resolved simulations, Rai et al 33 and Kim et al 34 demonstrated that the characteristics of mesoscale features determine the macroscopic ignition behavior of HMX and polymer-bonded explosives (PBXs), respectively. These simulations, however, have not yet been extended to time or length scales over which a complete SDT process occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the scarcity of direct measurements probing these microscale mechanisms, numerical simulations provide insights on these phenomena. Numerical studies have investigated sensitivities to impact pressure, pore size, pore morphology, multiple pores and grains, anisotropic crystal plasticity, rate-dependent strength, melt viscosity, and chemical kinetics [7][8][9][10][11][12][13][14][15][16][17][18]. Only recently have experimental studies measured hot spot temperatures in shocked HMX [19][20][21].…”
Section: Introductionmentioning
confidence: 99%